O auto da liberdade: patrimônio histórico e cultural de Mossoró-RN: mitos fundadores e produção de identidades. - Alves, Axel Bezerra (2020)
Our work aims to analyze the importance of various events in the formation of the identity of the people of Mossoró, one of the most important cities in the interior of Northeast Brazil and, as historical events, contribute to the formation of an identity specific to a given urban community. . Therefore, we developed a work to show the City, the people and an important part of its History, which contributes to the formation of its own identity. The booklet developed in the form of a folder aims to awaken interest in history and even lead readers to a more in-depth reading about the History of Mossoró.